PENGARUH BERBAGAI MINUMAN TERHADAP STABILITAS WARNA RESIN AKRILIK - Amiyatun Naini (Fakultas Kedokteran Gigi Universitas Jember, 2011)
Acrylic Resin is often used in dentistry as denture. Colour stability of denture materials is one of primary factor for estetic. Acrylic denture bas is easy to permeate bevero know effect of coloring beverages in color stability. Colour changing of resin can be occurred by consuming colouring beverages, such as tea, coffee, wine, juice and chocolate. Colour changing of colour is not permanent in acrylic resin, and can be removed by brushing and polishing.